Relationship between ghrelin and thyroid disease: a meta-analysis - Xin, Caihong; Yao, Jiayi; Li, Huijuan; Sun, Xin; Wang, Huijuan (Frontiers in Endocrinology, 2025)
BackgroundPrevious studies have identified a close relationship between ghrelin levels and thyroid disease. Ghrelin levels were lower in patients with hyperthyroidism compared with healthy individuals, and increased after treatment. However, other studies have reported inconsistent results. As such, the association between ghrelin and thyroid disease remains controversial.MethodsA literature search of the Web of Science, Wiley Online Library, Embase, and PubMed databases was performed. The title or abstract search term “thyroid” was used in combination with “ghrelin”. Meta-analysis results are reported as standardized mean difference with corresponding 95% confidence interval (CI).ResultsTwenty-three studies were included in this meta-analysis. Ghrelin levels in patients with hyperthyroidism were significantly lower than those in healthy individuals (SMD: -1.03, 95% CI [-1.75, 0.32]), but significantly higher after effective treatment (SMD: 0.77, 95% CI [0.03, 1.51]). Ghrelin levels were higher, but not significantly, in patients with hypothyroidism compared with healthy controls (SMD: 0.48, 95% CI [-0.13, 1.08]).ConclusionsThis systematic review is the first to evaluate the relationship between ghrelin and thyroid disease. Determining the role of ghrelin in thyroid disease will significantly contribute to understand of symptom or pathomechanism.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024591501.